Effect of turkey berry (Solanum torvum) stalk extract on masculinization of guppy fish (Poecilia reticulata) - Nurhayati; Vicana Pandang Ivonda; Razi Fakhrul; Syahputra Faisal; Thaib Azwar; Handayani Lia (BIO Web of Conferences)
Turkey berry stalk contain steroid hormones. It has potential as one of the natural hormones for sex direction in fish. Sex direction aims to produce monosexed fish. Sex direction in fish is one of the genetic engineering. Guppy fish is one of the aquatic fishery commodities. The attraction of guppy fish lies in the beauty of its color, attractive and varied colors are obtained in male guppy fish. The aims of this study to determine the effect of masculinization of guppies using turkey berry stalk extract and the optimal dose on the percentage of male and female guppies. The experimental group used a Completely Randomised Design (CRD) with two factors and three replications. The first factor was is the length of time the broodstock was immersed (24 hours, 48 hours). The second factor is the dose of turkey berry stalk extract (50 ppm, 100 ppm, 200 ppm). The parameters observed included male of guppy larvae, female of guppy larvae and survival rate. The results showed that the optimal dose of turkey berry stalk extract to produce a percentage of male guppy fish in the immersion treatment with a time of 24 hours, a dose of 200 ppm of 66.47 ± 9.13%.